INNOVATIVE TECHNOLOGIES AS A SOCIOCULTURAL ASPECT OF PROMOTING PHYSICAL CULTURE AND SPORTS - Молотильнікова, В.; Ложенко, К.В. (Modern engineering and innovative technologies, 2024)
The article addresses the relevance of implementing innovative technologies in physical education and sports as a means of promoting a healthy lifestyle among youth. It analyzes the impact of distance learning, the COVID-19 pandemic, and military actions